Síntese da sílica MCM-41 usando um surfactante catiônico polimerizável e avaliação na transesterificação catalítica - Silva, Laura Lorena da (2014)
The masters work presented is result of a great effort provided by the group, which has worked with changes in the synthesis of CTA-MCM-41. The synthesis of the M41S family (composed of mesoporous silica MCM-41, MCM-48 and MCM-50) was developed by Mobil Oil Corporation in 1992 due to necessity to processing of molecules larger than 0.75 nm, which is the pore diameter of zeolite Y. Among the silica, the most studied is the MCM-41. When the MCM-41 containing cations CTA in your pores, has catalytic sites with basic character because of the presence of anions siloxy (≡SiO-) associated. In evaluating the basic character of the CTA-MCM-41 in transesterification reactions of monoesters, we obtained satisfactory conversions, but when catalyst was reused, there was loss of catalytic activity due to leaching of cations CTA. With the objective of providing more stability in catalytic transesterification reactions of monoester, have changed the routes of synthesis through the use of monomers like acrylate, methacrylate esters and styrene. For this particular research, arises the innovative proposal to replace the CTABr surfactant (Cetyltrimethylammonium bromide) used in the synthesis of mesoporous silica by the surfactant synthesized, CADMABr (Cetylallyldimethylammonium bromide), which differs from CTABr by the substitution of a methyl group of the hydrophilic head group by the polymerizable allyl group. To check the formation of the surfactant and the degree of polymerization solution was held elementary chemical analysis (CHN) and nuclear magnetic resonance of 13C (NMR 13C), it was done also the small angles X-ray scattering (SAXS) of dispersions of different concentrations of CTABr and CADMABr to compared the micellar behavior. For characterization of the catalysts synthesized with this new polymerizable surfactant (Surfmer) was held X-ray diffraction for phase identification characteristic of silica, electron microscopy and thermogravimetry. The results were promising, although the catalytic stability was not achieved in significant way yet. However, the study conducted opens up a range of possibilities for continuation of this theme, as the replacement CTABr by CADMABr makes possible the polymerization without inserting of monomers inside the micelles.